Beauty salon- a marketplace icon. Issue 6 (2nd November 2021) - Ourahmoune, Nacima; Jurdi, Hounaida El
ABSTRACT: Beautification rituals are powerful elements of consumer cultures that transcend time and place. In an age of "moral terrorism" to "invest" in the body as an imperative, beauty salons -a twentieth century invention- have become a ubiquitous resource for individuals' self-actualization through consumption. This market-mediated place dedicated to beauty services is less investigated than the extensive multidisciplinary literature available on beauty and the body. We argue in this paper that beauty salons achieve iconicity through the interplay of four critical dimensions that reinforce one another: (1) the spatial performances of withdrawal from the world, (2) the mediation of experiences of gendered intimacies, (3) the articulations of complex narratives of magical transformations, and (4) the subtle claims of medico-scientific truths that captivate consumers.